Pengaruh Game Edukasi Matematika Berbasis Wordwall Terhadap Motivasi Belajar Peserta Didik Fase E SMAS YLPI Pekanbaru - Atika, Yunisa; Amelia, Sindi (Perspektif Pendidikan dan Keguruan, 2024)
One of the factors that influence the success of students' learning is the role of learning motivation. Learning motivation makes students trigger the desire to do something to achieve maximum achievement. This can grow with the utilization of interactive learning educational game technology such as that used in this study, namely wordwall. This study aims to determine the effect of wordwall-based math educational games on the learning motivation of Phase E students of SMAS YLPI Pekanbaru. This research is an experimental research using nonequivalent control group design and phase E as the research population. Sampling using saturated sampling technique with class X1 as experimental class and X2 as control class. Data obtained through questionnaire sheets and supported by teacher observation sheets. Hypothesis testing in this study used t-test. The findings of this study indicate that class X1 as an experimental class has a higher category than class X2 which is analyzed by descriptive analysis. The results of the hypothesis based on the t-test showed that tcount = 2.57 > ttable = 1.68 with a significance of 0.014 < 0.05. Thus, H0 is rejected and H1 is accepted, which means that there is an effect of wordwall-based math educational games on the learning motivation of phase E students of SMAS YLPI Pekanbaru.